PENGELOLAAN DATA PENDISTRIBUSIAN TECHNICAL DAN ELECTRICAL SUPPLY BERBASIS WEB PADA PT.KARUNIA ABADI PADANG (KAP) - Stefani Hardiyanti Putri; Wizra Aulia (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
This research was motivated by the problems of manual data processing and goods distribution at PT. Karunia Abadi Padang (KAP), which resulted in stock calculation errors, report discrepancies, and lengthy data searches. The purpose of this study is to develop a web-based system to improve the efficiency, accuracy, and speed of the goods distribution data processing process, as well as to minimize errors. The methods used are field research with interviews and direct observation at PT. KAP, as well as literature research with the Waterfall SDLC model approach. The developed system uses PHP and MySQL technology for integrated and real-time data management, enabling online goods distribution. The results of the study show that the implementation of this system reduces data processing and information search time by up to 50%, reduces stock calculation errors, and produces more accurate reports that can be accessed directly. In addition, this system reduces dependence on manual recording, increases time efficiency, and lowers operational costs. The scientific contribution of this research is the development of a methodology for the application of web-based systems in the management of goods distribution in small to medium-sized distribution companies, as well as providing empirical evidence of the positive impact of web-based systems on operational efficiency and error reduction in the context of goods distribution. This research can be used as a reference for the development of similar systems in other distribution companies facing similar problems.